Event registration system for INR Linac - Grekhov, O.V.; Drugakov, A.N.; Kiselev, Yu.V. (Вопросы атомной науки и техники, 2006)
The software of the Event registration system for the linear accelerator is described. This system allows receiving
of the information on changes of operating mode of the accelerator and supervising of hundreds of key parameters of
various systems of the accelerator. The Event registration system consists of the source and listeners of events. The
sources of events are subroutines built in existing ACS Linac. The listeners of events are software Supervisor and
Client ERS. They are used for warning the operator about change controlled by parameter of the accelerator Система регистрации событий это пакет программного обеспечения. Она позволяет оперативно получать информацию об изменениях в режиме работы ускорителя, контролируя более сотни основных параметров различных технологических систем ускорителя. Система регистрации событий состоит из источников и приемников событий. Источниками событий являются подпрограммы, встраиваемые в существующую АСУ ЛУ. Приемниками событий служат программы Диспетчер и Клиент СРС, предназначенные для оповещения оператора об изменении контролируемых параметров. Система реєстрації подій це пакет програмного забезпечення. Вона дозволяє оперативно отримувати інформацію про зміни в режимі роботи прискорювача, контролюючи більше сотні основних параметрів різних технологічних систем прискорювача. Система реєстрації подій складається із джерел і приймачів подій. Джерелами подій є підпрограми, що вбудовуються в існуючу АСУ ЛП. Приймачами подій є програми Диспетчер і Клієнт СРС, що призначені для оповіщення оператора про зміну контрольованих параметрів.